DAMPAK PEMBERIAN INSENTIF FINANSIAL DALAM MENINGKATKAN KINERJA KARYAWAN DENGAN WORK ENGAGEMENT SEBAGAI VARIABEL INTERVENING DI BMT USAHA ARTHA SEJAHTERA PAMOTAN - Elfayet, Tsaniya Almer; Hana, Kharis Fadlullah (Media Riset Bisnis & Manajemen, 2023)
This study aimed to determine financial incentives, employee performance, and work engagement; the influence of financial incentives on employee performance; the influence of financial incentives on work engagement; the influence of work engagement on employee performance; and to find out whether work engagement mediates financial incentives on the performance of BMT Usaha Artha Sejahtera Pamotan employees. This research is quantitative. The sample used in this research was employees at BMT Usaha Artha Sejahtera Pamotan. The sample used in this research was 50 respondents. The data collection technique uses a questionnaire. The data analysis technique used is path analysis using the Statistical Product and Service Solutions (SPSS) software program version 26. Financial incentive variable is in the good category, employee performance is in the high category, and work engagement is in the very high category. The results of this research show that financial incentives have a positive and significant effect on employee performance. Financial incentives have a positive and significant effect on work engagement. Work engagement has a positive and significant effect on employee performance. Work engagement can mediate the effect of financial incentives on employee performance. This research makes a new contribution by emphasizing the importance of work as a mediating variable in the context of providing financial incentives, an approach that has rarely been researched in depth in the microfinance sector. Thus, these findings are relevant for the development of more effective human resource management strategies, especially in the cooperative sector and microfinance institutions.